Role of vimentin in regulation of monocyte/macrophage differentiation - Benes, Petr; Macecková, Vendula; Zdráhal, Zbynek; Konecná, Hana; Zahradnícková, Eva; Muzík, Jan; Smarda, Jan (Differentiation; research in biological diversity, 2006)
Maturation of blood cells depends on dramatic changes of expression profiles of specific genes. Although these changes have been extensively studied, their functional outcomes often remain unclear. In this study, we explored the identity and function of an unknown protein that was greatly overexpressed in v-myb-transformed BM2 monoblasts undergoing differentiation to macrophage-like cells. We identified this protein as vimentin, the intermediate filament protein. We show that an increased level of vimentin protein results from activation of the vimentin gene promoter occurring in monoblastic cells induced to differentiate by multiple agents. Furthermore, our studies reveal that the vimentin gene promoter is stimulated by Myb and Jun proteins, the key transcriptional regulators of myeloid maturation. Silencing of vimentin gene expression using siRNA markedly suppressed the ability of BM2 cells to form macrophage polykaryons active in phagocytosis and producing reactive oxygen species. Taken together, these findings document that up-regulation of vimentin gene expression is important for formation of fully active macrophage-like cells and macrophage polykaryons.
Keywords: kur domácí; Animals; 2D gelová elektroforéza; transkripční faktory; Chickens; makrofágy; Up-Regulation; Fibroblasts; Genes, jun; Cell Line, Transformed; buněčná diferenciace; vimentin; Macrophages; křepelky a křepelovití; monocyty; protoonkogenní proteiny c-jun; upregulace; Transcription Factors; Vimentin; fibroblasty; Oncogene Proteins v-myb; hmotnostní spektrometrie; Tetradecanoylphorbol Acetate; Quail; onkogenní proteiny v-myb; regulace genové exprese; Hematopoiesis; Monocytes; Electrophoresis, Gel, Two-Dimensional; Mass Spectrometry; Proto-Oncogene Proteins c-jun; hematopoéza; Cell Differentiation; tetradekanoylforbolacetát; promotorové oblasti (genetika); zvířata; Gene Expression Regulation; Promoter Regions, Genetic; geny jun; transformované buněčné linie